URA MAWASHI GERI KICK SKILLS TRAINING MODEL FOR KARATEKA AGES 13-15 - Hasim, Muhamad Puad; Lubis, Johansyah; Widiastuti, Widiastuti (Universitas Negeri Semarang, 2025)
Introduction: This study aims to develop a training model for ura mawashi geri kicking skills specifically designed for karateka aged 13-15 years. Objectives: The research background is motivated by the low effectiveness of ura mawashi geri kicks in karate competitions, despite this technique having high strategic value in martial arts performance. Method: The research methodology employed Research & Development approach using the ADDIE model, conducted at GOR Kelapa Gading, DKI Jakarta, during June-July 2025. The research subjects consisted of 30 karate athletes aged 13-15 years selected through purposive sampling technique with specific inclusion criteria including minimum 2 years karate training experience and absence of injury. The research instrument utilized validated ura mawashi geri kicking skill tests that had been evaluated and approved by martial arts experts. Data analysis employed both qualitative and quantitative approaches, with statistical significance testing conducted using paired-samples t-test and descriptive statistics for central tendencies analysis. Result: The research results demonstrated significant improvement from the pre-test average score of 76.00 to 89.06 in the post-test following the implementation of 15 specialized training models over 8 training sessions. Conclusion: The developed training model proved to be feasible and effective for enhancing ura mawashi geri kicking skills among karateka aged 13-15 years, providing valuable insights for martial arts training methodologies and competitive performance improvement.